Investigating the Superoxide Formation and Stability in Mesoporous Carbon Perovskite Solar Cells with an Aminovaleric Acid Additive. (7th February 2020) - Péan, Emmanuel V.; De Castro, Catherine S.; Dimitrov, Stoichko; De Rossi, Francesca; Meroni, Simone; Baker, Jenny; Watson, Trystan; Davies, Matthew L.
Abstract: Perovskite solar cells have attracted a great deal of attention thanks to their high efficiency, ease of manufacturing, and potential low cost. However, the stability of these devices is considered their main drawback and needs to be addressed. Mesoporous carbon perovskite solar cells (m‐CPSC), consisting of three mesoporous layers (TiO2 /ZrO2 /C) infiltrated with CH3 NH3 PbI3 (MAPI) perovskite, have presented excellent lifetimes of more than 10 000 h when the additive NH2 (CH2 )4 CO2 HI (5‐ aminovaleric acid iodide; 5‐AVAI) is used to modify the perovskite structure. Yet, the role of 5‐AVAI in enhancing the stability has yet to be determined. Here, superoxide‐mediated degradation of MAPI m‐CPSC with and without the 5‐AVAI additive is studied using the fluorescence probe dihydroethidium for superoxide detection. In situ X‐ray diffractometry shows that aminovaleric acid methylammonium lead iodide (AVA‐MAPI) perovskite infiltrated in mesoporous layers presents higher stability in an ambient environment under illumination, evidenced by a slower decrease of the MAPI/PbI2 peak ratio. Superoxide yield measurements demonstrate that AVA‐MAPI generates more superoxide than regular MAPI when deposited on glass but generates significantly less when infiltrated in mesoporous layers. It is believed that superoxide formation in m‐CPSC is dependent on a combination of competitive factors including oxygen diffusion, sample morphology, grain size, and defect concentration. Abstract : Superoxide formation in mesoporous carbon perovskite solar cells is dependent upon a combination of competitive factors including defect concentrations, charge carrier extraction, oxygen diffusion, and grain morphology. The addition of 5‐aminovaleric acid iodide to the methylammonium lead iodide perovskite allows the formation of smaller grains, thus hindering oxygen diffusion in the film, reducing superoxide formation.